Pain management in patients with cirrhosis. Issue 6 (26th July 2018) - Rakoski, Mina; Goyal, Preeya; Spencer‐Safier, Michelle; Weissman, Jill; Mohr, Gina; Volk, Michael
Abstract : Watch a video presentation of this article Answer questions and earn CME